IMPACT ASSESSMENT OF THE UNIVERSITY STUDENT COUNSELING SERVICE FOR STUDENTS RISK DUE TO POOR ACADEMIC PERFORMANCE - Muñoz Valera, Paola (2013)
This article presents the evaluation of the UPC Student Tutorial Service of for students with apoor academic performance and who are at risk of being dismissed from the university. This studyaims at investigating the students perception of the tutorial service when they are at academic risk,taking into account their attendance and how they overcame the risk. Semi-structured interviews werecarried out with 24 students at academic risk and the study of their perceptions was based on fourdimensions: general services, methodology, facilitator and suggestions. The results reveal that moststudents regardless of their risk status or attendance, appreciate the service, especially the supportprovided by the university and the facilitator as well as providing their suggestions to implement theservice. The results are discussed based on the theoretical approach of the tutorial services provided.